The transatlantic introduction of weakfish Cynoscion regalis (Bloch & Schneider, 1801) (Sciaenidae, Pisces) into Europe - Morais, Pedro (2016)
Weakfish Cynoscion regalis (Bloch and Schneider, 1801) is a sciaenid fish native to the east coast of North America and has been recently collected in three areas of the Iberian Peninsula (Europe). We aimed to i) provide the first report of the presence of weakfish in Europe, ii) hypothesize the most likely introduction vector, iii) discuss the potential for ecological overlap between weakfish and meagre Argyrosomus regius (Asso, 1801), the native Sciaenidae species, and iv) highlight the importance of citizen science in the detection of nonnative species. Weakfish were captured in the Sado estuary (July 2014), Gulf of Cadiz (November 2015) and the adjacent Guadiana estuary (June 2016), and in two Galician Rías (June 2016). Anglers reported that weakfish was present in the Sado estuary for “some” years, while their presence was only noticed recently in the other two areas. We hypothesize that ballast water was the introduction vector, that weakfish established a reproducing population in the non-native range, and that it dispersed from the Sado estuary, a central region of its current distribution range. The Sado estuary might have been the introduction area for weakfish via ballast water because there is a busy transoceanic commercial port in the estuary. Moreover, they are not used in European aquaculture facilities, nor in the aquarium trade. The collected specimens were ≤50 cm, with average lengths of 30 cm, which corresponds to a median age of 2 years and to individuals capable of reproducing. As a result, the year of introduction must be before 2012. Weakfish have a similar ecological niche to meagre, but the outcome of potential interactions is uncertain. Citizen science, especially the initiative of local fishermen, was critical to detect this non-native species.